Ars Celebrandi dalam Perspektif Paus Benediktus XVI - Dominikus Doni Ola; Antonius P Sipahutar; Fincer Wesman La’ia (Journal New Light, 2025)
The main issue that is the focus of this study is what is the essence of the liturgy in the Catholic Church and how the Ars Celebrandi liturgy is in the perspective of Pope Benedict XVI. Therefore, this study wants to explore two important things, namely how a Catholic personally and communally understands the liturgy and how it was initiated by Pope Benedict through the theme of Ars Celebrandi. This research uses library research, which is supported by reference sources, especially Church documents and studies on the theme of liturgy and the Eucharist. Data and information are processed by researchers by sorting and examining the main ideas and classifying them in special themes according to the research objectives. This study found that Ars Celebrandi is the art of celebrating liturgical celebrations appropriately and can help the faithful to internalize all the mysteries of the faith that are celebrated in the liturgical celebration system so that in the end all the faithful can participate in the entire celebration of faith. Therefore, all liturgical leaders need to celebrate the liturgy according to the rules of the liturgy itself without having to improvise and be creative according to personal interpretation. Ars Celebrandi is closely related to the meaning of the mystery of faith, namely the encounter with God present in the liturgical celebration. Ars Celebrandi does not stop at the issue of how the liturgical celebration becomes a stunning display. However, Ars Celebrandi is more about the appreciation of the mystery of faith in oneness with God that is present in the liturgical celebration. This study is expected to add to the scientific treasures in the field of Catholic theology, especially those related to the meaning and significance of beauty in the liturgy of the Eucharist.